Analysing the actions of the rebels in the English Revolt of 1381: The case of Cambridgeshire. (22nd November 2021) - Xu, Mingjie
Abstract: This article throws new light on the forces that propelled the Peasants' Revolt of 1381 by focusing closely on the actions of the rebels, the number and nature of the attacks they carried out, and the identities, status, and roles of their victims. The exceptionally rich and comprehensive records of the violence and disorder that occurred in Cambridgeshire have been systematically studied and each incident analysed, categorized, and quantified. The results reveal that attacks in this region were overwhelmingly directed against political and judicial officials operating at a national and local level, and that attacks against landlords arising from oppressive manorial lordship constituted less than one‐tenth of recorded violent incidents. The use of similar analysis of the actions of rebels recorded in the judicial proceedings of revolts in other regions may lessen the scale of the contention that still exists over the grievances that provoked this momentous uprising and who the rebels judged to be their main adversaries.